Differential diagnosis and treatment of thyroid storm - YAN Huixian, LÜ Chaohui (Zhenduanxue lilun yu shijian)
Thyroid storm is a rare, life-threatening endocrine emergency characterized by severe clinical manifestations of thyrotoxicosis. Studies in the United States and Japan show that the annual incidence rates of hyperthyroid storm are (0.57-0.76) per 100 000 people and 0.2/100 000 people, respectively, accounting for 0.22% of all hyperthyroid patients and 5.4% of hospitalized hyperthyroid patients. Even with timely treatment, the mortality rate of patients with hyperthyroidism storm is still as high as 10%-30%; If left untreated, the mortality rate of patients may reach 90%. The misdiagnosis and missed diagnosis rate of hyperthyroidism storm in the Emergency Department is as high as 43.48%. It may be precipitated by abrupt discontinuation of antithyroid drugs or by an acute event such as infection, trauma, thyroid or nonthyroidal surgery, an acute iodine load, or parturition and other rare causes. There are currently no recognized standards or validated clinical tools for diagnosing thyroid storm. The diagnosis of thyroid storm is based upon the presence of biochemical evidence of hyperthyroidism (elevation of free T4 and/or T3 and suppression of TSH), and severe and life-threatening symptoms (hyperpyrexia, cardiovascular dysfunction, and altered mentation). BWPS has been widely used for the identification of thyroid storm for nearly 30 years. The main treatments for thyroid storm consist of symptomatic treatment and specific treatment for the thyroid gland, including removing the cause and treating complications cuse of thionamide, iodine, glucocorticoids and beta-blockers to inhibit new hormone synthesis, block the peripheral conversion of T4 to T3, inhibition of the release of thyroid hormone. If the above treatment do not improve the condition, blood purification therapy (plasmapheresis) can be tried. In addition to specific therapy directed against the thyroid, supportive therapy is essential. After active treatment, most of the status of patients with thyroid storm are improved within 1 to 2 days. After a successful rescue of thyroid storm, hyperthyroidism should be treated by radical treatment.